Communication Situation and the Succession Category of Etiquette Formulae - AGHAJANYAN, ZARIK (Bulletin of Yerevan University B: Philology, 2021)
Speech formulae form an indivisible part of the etiquette. Their examination should be based on the speech situation. The latter has practically not been studied in Armenian linguistics. Etiquette formulae are divided into different communicative-semantic fields. In the system of speech etiquette, the logical succession is of no minor importance: it is important that one should follow the rules standardizing the category of succession, which, of course, are not inviolable. The formulaic system defined by the speech etiquette is not only the reflection of the present state of any language but also its everlasting guideline.